Assumption, Union and Sanctification: Some Clarifying Distinctions. (3rd November 2016) - King, Rolfe
Abstract: In this article I engage with the notion that Christ ought to be understood to have a fallen human nature because Christ sanctifies human nature, and it is fallen humanity that needs sanctifying. In opposition to this line of thought, I argue that the Son of God assumed an unfallen nature, but with the powers of fallenness operative within it, and that this notion is consistent with a distinct account of sanctification. In support of these claims, I develop distinctions between a conjoining union and a transferring union, and between the Chalcedonian union at the incarnation and the extension of that union on the cross. At the assumption a conjoining union occurred, not a transferring union. Christ sanctified his own nature, prior to a transferring union.